The Changing Role of the Department Chair - Dean Ann Tate; Kim DeLauro Dr.; Dawn Eaton Dr. (Academic Chairpersons Conference Proceedings, 2018)
At San Jacinto College, the department chair role has changed significantly from the traditional model. Expanded to a twelve-month position, chairs commit to coaching faculty, engaging in strategic initiatives, and other special projects designed to improve student success. Benefits of enhanced supervision, strategic planning, and innovative projects will be discussed.
Keywords: Academic leadership; Faculty development; Student Success; Strategic planning; Enrollment analysis